2017
DOI: 10.1016/j.ecolind.2017.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure and neighbor linear features influence more carabid functional diversity in olive groves than the farming system

Abstract: A B S T R A C TThe effects of land-use management and environmental features at different scales on carabid beetle diversity and trait structure were assessed across olive groves in northeastern Portugal. We selected organic and integrated olive groves that were distinct in terms of specific management practices, local linear features and landscape configurations. Besides the management intensification levels, differences in carabid diversity and community traits were mainly due to local habitat and ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Indeed, using emergence traps, Boinot et al (2019b) showed that carabids overwintering in UVS are larger than those associated with crop alleys. This result was consistent with previous studies showing that large carabids are more sensitive to agricultural disturbances (Winqvist et al, 2014;da Silva et al, 2017).…”
Section: Positive Effects Of Alley Cropping Agroforestry On Generalissupporting
confidence: 93%
“…Indeed, using emergence traps, Boinot et al (2019b) showed that carabids overwintering in UVS are larger than those associated with crop alleys. This result was consistent with previous studies showing that large carabids are more sensitive to agricultural disturbances (Winqvist et al, 2014;da Silva et al, 2017).…”
Section: Positive Effects Of Alley Cropping Agroforestry On Generalissupporting
confidence: 93%
“…Paredes et al (2013a) showed that the abundance of natural enemies was, in general, more influenced by herbaceous and large woody vegetation adjacent to the crop than by small woody vegetation. Martins da Silva et al (2017) found that carabid species varied with the specific management practices in the olive grove as well as with local and linear features around the groves. However, Albertini et al (2016) did not find significant correlations between the occurrence of natural areas close to the olive groves and the abundance of predaceous Coleoptera in the crop area.…”
Section: Introductionmentioning
confidence: 99%
“…Body size is a key trait related to several physiological, life-history, and ecological features. Within insects, body size would be associated to characteristics such as sensitivity and tolerance against disturbances, home range, spatiotemporal distribution, or dispersal ability, a dominant factor in shaping arthropod communities within agricultural systems [44,45,54,[72][73][74]. Small size arthropods have less resource requirements and are comparatively more tolerant than large size arthropods, which associate with more stable habitats [74].…”
Section: Response Of Morphometric Traitsmentioning
confidence: 99%
“…However, it is noteworthy that not all traits are related to the same ecological features. For example, body size is related to attributes such as dispersal ability, sensitivity and response to habitat disturbance, as well as spatial niche or trophic, competitive, and facilitative relationships within ecological networks [44,54]. By contrast, body shape is associated with microhabitat use, while femur shape and wing length are related to dispersal ability and disturbance avoidance.…”
Section: Introductionmentioning
confidence: 99%